Peran Guru PAI Sebagai Motivator dalam Meningkatkan Kedisiplinan Siswa Kelas XI di SMA Takhasus Al-Qur’an Kalibeber Wonosobo - Karimah, Hana Nur; Hamzah, Muchotob; Faisal, Vava Imam Agus (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This study aims to determine the role of PAI teachers as motivators in improving the discipline of class XI students at SMA Takhasus Al-Quran Kalibeber Wonosobo. To find out the supporting and inhibiting factors of the role of the PAI teacher as a motivator in improving the discipline of class XI students at SMA Takhasus Al-Quran Kalibeber Wonosobo. The type of research used is descriptive qualitative. Collecting data through observation, interviews, documentation. Data analysis through data collection, data reduction, data presentation, and conclusions. The results showed that the role of the PAI teacher was optimal in playing his role as a motivator in increasing student discipline. Namely being a motivator, role model, always giving direction and advice. This is indicated by the increase in student discipline. The discipline level of class XI students at SMA Takhasus Al-Quran Kalibeber Wonosobo is said to have increased marked by the existence of several disciplinary indicators including, discipline in entering school, discipline in entering class, study discipline, discipline in discipline. Supporting factors for PAI teachers as motivators in improving student discipline are: adequate facilities and infrastructure, school regulations, educators, students, the environment, while the inhibiting factors are: environment, lack of co-workers.